POTENSI SOSIAL EKONOMI DESA TERTINGGAL DI KALIMANTAN TENGAH SEBAGAI SEBUAH DATASET - Gaffar, Ummu Habibah (Jurusan Ilmu Pemerintahan Universitas Palanfka Raya, 2024)
This article presents a dataset derived from research aimed at mapping the socio-economic potential of two underdeveloped villages, Sei Bakau and Sei Hambawang, located in Sebangau Kuala District, Pulang Pisau Regency, Central Kalimantan. Data were collected through document studies, non-participant observation, and in-depth interviews. The dataset highlights socio-economic potentials that can serve as assets, offering opportunities for the development and advancement of underdeveloped villages.